Reflections on Mother Tongue Education in National and Provincial Policies in Mainland China - Liu, Qing (My University, 2018)
China, as a culturally and linguistically diversified country, has 56 official recognized ethnicities and languages from six different language families. Ever since the establishment of the People’s Republic of China, the right for people of different ethnicities to receive education in their mother tongues has been guaranteed by the Constitution. However, due to the strong support from the central government, Mandarin gradually gains its official status and influence in the field of public service, mass media, and education. Not only regional varieties of Chinese language has been replaced by Mandarin in all the formal education, but ethnic languages have also shifted from the teaching languages to an independent subject. Therefore, this study tries to reflect the mother tongue education (MTE) among speakers of Chinese languages and non-Chinese languages by analyzing the national and provincial policies in depth. The main focuses are how MTE is regulated and organized in both national and provincial policies and how national and provincial policies correspond to each other. Since the education systems in Mainland China, Hong Kong, Macau, and Taiwan are under the supervision of separate governments, this study will only focus on the national and provincial policies from Mainland China. The structure of this thesis is as follows. Chapter 1 introduces the previous research on language education policies in Mainland China and Chapter 2 to 4 present the basic information of languages and MTE in Mainland China. Chapter 5 explains the research method in detail and introduces the cases chosen for this study. The analysis of the national and local level policies will be presented in Chapter 6, and the reflections on MOI policies in educational, political and social-economic sphere will be discussed in Chapter 7. Finally, Chapter 8 will serve as concluding part to summarize the findings.
Keywords: Mother tongue education, medium of instruction, policy analysis, China